Evaluation of Preservative Properties in Psidium Guajava Leafs Using Hydro-Alcoholic Extraction - Jamaluddin, Jafni (2007)
A preservative is a natural or synthetic chemical that is added to products such as foods, pharmaceuticals, paints, biological samples, etc. To retard spoilage, whether from microbial growth, or undesirable chemical changes. Typically copper, borate, and petroleum based chemical compounds are used.